Pemanfaatan Kapabilitas Konsultan Pajak dalam Pemeriksaan Pajak Penghasilan: Studi Kasus berdasarkan Perspektif Relational View - David David; Heru Tjaraka (Politeknik Ganesha Medan, 2026)
Tax audits play an important role in assessing corporate compliance and determining final tax liabilities. Companies often face internal capability limitations when explaining their tax positions to the authorities. This study addresses the primary question of how tax consultant assistance influences audit outcomes, particularly the value of tax adjustments and the final tax liabilities after the discussion process. The purpose of this research is to analyze the benefits of tax consultant assistance by comparing the 2022 tax audit handled internally with the 2023 audit supported by a consultant. The study was conducted at PT DCP using a descriptive qualitative method. Data were collected through documentation and semi structured interviews with four informants directly involved in the audit process. The analysis was carried out by mapping the findings to four mechanisms of the Relational View, namely relation-specific assets, knowledge-sharing routines, complementary resources, and effective governance. The results show a notable reduction in tax adjustments, from 30.24% in the 2022 tax year to 8.59% in 2023. The approval rate of restitution increased from 9.48% to 82.29%. Consultant assistance improved the clarity of arguments, strengthened coordination, and reduced misinterpretation of the auditor’s requests. This study contributes by demonstrating that strategic collaboration between companies and tax consultants has a direct impact on the effectiveness of the audit process and its final outcomes.